Pemisahan Emas Pada Video Graphic Array (VGA) Komputer Dengan Metode Elektrolisis Dan Presipitasi - Muhammad Nur Rahim Sjam; Yusnimar Yusnimar; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Gold has been using in electronics and telecommunication industry, for example, Video Graphic Array (VGA) computer. To get the maximum results in the separation of the gold used variations potential difference ( 6; 9; 12 volt ) and the type of precipitant (NaHSO3 and H2C2O4) . In this study, 5 gram of samples VGA is electrolyzed by using H2SO4 for 1 hour. The precipitate formed is separated from the filtrate. The precipitate was dissolved in Aqua Regia at a temperature of 70˚C for 30 minutes further diluted with Aqua DM until the volume is 50 mL . Au concentration was analyzed by AAS (Atomic Absorption Spectrophotometry) and Au deposited with NaHSO3 and H2C2O4 . Based on the analysis result, the maximum Au concentration at the former VGA computer is equal to 181,36 ppm. For 5 grams of the sample , the maximum weight of Au precipitate obtained 1,07 grams by using NaHSO3 as a precipitant .Keywords : Au, VGA computer, Electrolysis, Precipitant